SAPHO and CRMO: The Value of Imaging - Jurik, Anne Grethe; Klicman, Rikke Fuglsang; Simoni, Paolo; Robinson, Philip; Teh, James (Seminars in Musculoskeletal Radiology, 2018)
The syndromes synovitis, acne, pustulosis, hyperostosis, and osteitis (SAPHO) and chronic recurrent multifocal osteomyelitis (CRMO) constitute a group of chronic relapsing inflammatory osteoarticular disorders with frequently associated skin eruptions such as palmoplantar pustulosis and acne conglobata and rather characteristic imaging features in the form of osteitis and/or hyperostosis. CRMO predominantly occurs in children/adolescents and SAPHO in adults. Any skeletal site can be involved, and the imaging appearances vary, depending on the patient's age and the stage/age of the lesion. The diagnosis may be difficult if there is no skin disease, but attention to characteristic imaging appearances may help avoid misdiagnosis (e.g., infection and tumor) and thereby unnecessary invasive procedures as well as facilitating early diagnosis and appropriate treatment. This article provides an overview of the radiologic appearances of SAPHO/CRMO and relevant pathogenetic, clinical, and pathologic features to facilitate the diagnosis that often requires an interdisciplinary approach including radiologists.
Keywords: SAPHO; CRMO; osteitis; hyperostosis; spondyloarthritis